The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1590/0004-282x20190055
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and spirituality in patients with epilepsy

Abstract: Religiosity and spirituality (R/S) are widely regarded as important allies against illness and suffering in general. Findings in temporal lobe epilepsy (TLE) suggest the temporal lobe as the anatomical-functional basis of religious experiences. Both R/S are relevant in patients with epilepsy (PWE) since epilepsy can lead to psychosocial issues for a significant portion of patients and their families. Objective: To investigate R/S in PWE, as well as the impact of different epileptic syndromes on patients' R/S.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 31 publications
0
5
0
1
Order By: Relevance
“…7,20 The spiritual experience did not differ according to the epileptic syndrome. Some studies have described hyperreligiousness and greater religious conviction 12,15,16 and greater spirituality in TLE-HS. 14,16 However, other studies have found no difference in spirituality according to temporal or extratemporal epilepsy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,20 The spiritual experience did not differ according to the epileptic syndrome. Some studies have described hyperreligiousness and greater religious conviction 12,15,16 and greater spirituality in TLE-HS. 14,16 However, other studies have found no difference in spirituality according to temporal or extratemporal epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have described hyperreligiousness and greater religious conviction 12,15,16 and greater spirituality in TLE-HS. 14,16 However, other studies have found no difference in spirituality according to temporal or extratemporal epilepsy. 15 There was an association between a greater perception of spiritual experiences and EA in the right hemisphere, in the EEG.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spirituality is a more personal and existential construct of belief in (or relationship with) a higher power or divinity, involving the search for self-knowledge and philosophical questioning of the existence of the universe and life (10) . Religiosity, on the other hand, includes personal beliefs (in divinity or a higher power) gathered by an organized system of symbols and practices as a means of approaching the metaphysical and transcendental dimension through institutional practices, belonging and doctrinal commitments to churches or organized religions (11)(12)(13) .…”
Section: Introductionmentioning
confidence: 99%
“…O termo espiritualidade, enquanto distinto de religião ou religiosidade, é considerado um conceito recente no mundo ocidental que data da década de 1960 (9) A espiritualidade trata-se de um construto de dimensão mais pessoal e existencial de crença em (ou relação com) um poder superior ou divindade, envolvendo a busca pelo autoconhecimento e questionamento filosófico da existência do universo e da vida (10) . Já a religiosidade inclui crenças pessoais (em divindade ou um poder superior) capturadas por um sistema organizado de símbolos e práticas como meio de se aproximar da dimensão metafísica e transcendental mediante práticas institucionais, de pertença e compromissos doutrinários junto a igrejas ou religiões organizadas (11)(12)(13) .…”
Section: Introductionunclassified